EFEKTIVITAS DAN DAMPAK PROGRAM BANTUAN PRODUKTIF USAHA MIKRO (BPUM): UPAYA PENINGKATAN PRODUKTIVITAS UMKM PEKALONGAN - Gunawan, Ade; Nugraha, Aditya Agung (UIN Sunan Kalijaga, 2023)
The effectiveness of the BPUM program can seen from the inputs, processes, and outputs of MSMEs. Whether the BPUM program can also have impact on the productivity of MSMEs. This research is a type of descriptive research will describe symptoms, events or facts accurately and systematically related to the nature of the population. The approach used is qualitative. Qualitative research is conducted through natural observation, namely seeing, observing, and analyzing a problem, then examined in depth without statistical testing. The results of the study stated that BPUM had a positive impact on the productivity of MSMEs after the Covid-19 pandemic. Many business actors can rebuild businesses that are almost bankrupt, and can used as additional capital for business development. However, BPUM is not yet considered 100% effective because of weak supervision so that there are still misdirected funds. The BPUM program when viewed from inputs, processes, and outputs in several MSMEs in the Pekalongan Prefecture has a level of effectiveness with a percentage of fifty-fifty. The distribution of BPUM funds has a positive impact on the productivity level of MSMEs. BPUM funds are used as additional business capital, so that businesses can be developed and maintained by their respective owners.